Unveiling Epidemiologic Insights: A Case–Control Study of Congenital Cleft Lip and/or Palate Using Association Rule Mining. - Delshad, Salaheddin; Mousavi, Seyed Mohsen Laal; Alidadi, Maryam; Sabahi, Azam; Hajavi, Abazar; Ayyoubzadeh, Seyed Mohammad; Rezayi, Sorayya; Shahmoradi, Leila; Banerjee, Baisakhi (BioMed Research International, 2026)
Background: Cleft lip and/or palate (CLP) is one of the most prevalent birth abnormalities and is caused by incomplete growth and failure to close components of the face. The objective of this study was to describe the epidemiologic features of patients with congenital CLP and identify risk factors associated with the disorder. Methods: The study used the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) checklist for reporting on 1341 CLP patient records from MOHKAM Institute in Iran. We conducted a descriptive analysis on records spanning from September 2006 to May 2023. After applying eligibility criteria, 950 CLP cases and 950 controls with other congenital conditions were included. Data preprocessing removed bias. We then analyzed the preprocessed dataset using descriptive statistics, association rule mining (ARM), and the Apriori algorithm. Results: The study revealed that 88% of mothers did not use cosmetics during pregnancy. Additionally, 9% of cases had a history of disease during pregnancy, and 6% had a history of drug use. The study also examined the birth order of children and found that the highest number of children with congenital diseases occurred between the first and third children of the family. The age distribution of mothers showed the highest frequency in the age range of 18–24 years in both the case and control groups, whereas the frequency of fathers was highest in the age range of over 41 years. ARM identified five association rules with confidence values exceeding 0.567, indicating moderate associations between combined demographic and geographic variables and CLP occurrence. The rules demonstrated weak‐to‐moderate lift values, suggesting nonrandom associations within the dataset. Conclusion: Several maternal and familial factors, including pregnancy‐related conditions and parental age, were associated with CLP. Given the multifactorial nature of CLP and its susceptibility to multiple genetic and environmental influences, further large‐scale and multicenter studies are required to validate these associations and explore additional contributing factors.